Bioassay and histopathological effects of water-soluble fractions of crude oil on Coptodon guineensis (Nigerian Journal of Physiological Sciences, 2025)
Acute and subacute effects of crude oil's water-soluble fraction (WSF) and associated histopathological changes in the gills and liver of juvenile Coptodon guineensis were investigated. An acute toxicity test (96 hrs) was performed by a static non-renewal method at various concentrations of 0.25, 1, 5, 15, and 30%. Similarly, test organisms were tested in 2.5% sublethal concentration for 28 days. Water quality parameters, heavy metals, and total polycyclic aromatic hydrocarbons (PAHs) were determined using standard methods. After fish exposure in WSF of crude oil, gills and liver were harvested, stained with hematoxylin/eosin, and later prepared for photomicrography. Results revealed the LC50 as 26.73% (26.73 g/L), while total PAHs and heavy metal (Ni, Cd, and Pb) levels varied significantly (p < 0.05) in Coptodon guineensis over the period of exposure. Histopathological alterations were evident in gills and further revealed the presence of deformed secondary lamellae, with corresponding congestion of the passive central vein and cytoplasmic vacuolation in the liver. Apart from toxicity values to unravel the adverse impacts of the bioavailable water-soluble fraction of crude oil on juvenile Coptodon guineensis, the histopathological assay revealed underlying sub-lethal responses that can serve as early warning signals.Keywords: Bioassay, water-soluble fraction, crude oil, histopathological, Coptodon guineensis